Pembelajaran Dan Pelatihan Pembuatan Simulasi Jaringan Berskala Kecil (LAN) Dengan Software Cisco Packet Tracer - Fikry Farizi; Raka Devananda Saleh; An Nisa Amara Putri; Imam Yulmansyah; Rosyid Hendriartanto; Eligius Transparan Putra Zebua; Wisnu Firdaus; Yandi Ferdiansyah; Fawwaz Adnan; Nurhasanah (CV. Multi Kreasi Media, 2024)
Computer networks and Local Area Networks (LAN) are important foundations in modern information technology infrastructure, allowing electronic devices to connect to each other to share data and resources efficiently. LAN, which are commonly used in limited geographical areas such as offices or schools, play a key role in enhancing productivity and collaboration. However, when networks are not available, either due to infrastructure limitations or system failures, various problems such as limited access to information and collaboration arise, which hinder operational efficiency. This article examines the importance of training and learning to create small-scale network (LAN) simulations using Cisco Packet Tracer software. This study was conducted at SMP Islam Miftahul Huda to evaluate the impact and effectiveness of using network simulations in the teaching and learning process. With this training, users are expected to be able to understand network configuration, resource management, and troubleshooting, which will improve their ability to design, manage, and maintain computer networks. The results are expected to increase efficiency and productivity, as well as minimize potential problems in using LAN.